1997
DOI: 10.1094/phyto.1997.87.6.588
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Produced by the Rhizobacterium Pseudomonas aeruginosa 7NSK2 Induces Resistance to Leaf Infection by Botrytis cinerea on Bean

Abstract: De Meyer, G., and Höfte, M. 1997. Salicylic acid produced by the rhizobacterium Pseudomonas aeruginosa 7NSK2 induces resistance to leaf infection by Botrytis cinerea on bean. Phytopathology 87:588-593.Selected strains of nonpathogenic rhizobacteria can induce a systemic resistance in plants that is effective against various pathogens. In an assay with bean plants, we investigated which determinants of the rhizobacterium Pseudomonas aeruginosa 7NSK2 are important for induction of resistance to Botrytis cinerea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
1
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(162 citation statements)
references
References 32 publications
5
145
1
5
Order By: Relevance
“…2c). Some rhizobacteria trigger the SAR pathway by producing salicylic acid at the root surface 40,41 , and in other cases, ISR-inducing rhizobacteria trigger a different signalling pathway that does not require salicylic acid [42][43][44][45] .…”
Section: Systemic Resistance Induced By Non-pathogenic Rhizobacteriamentioning
confidence: 99%
“…2c). Some rhizobacteria trigger the SAR pathway by producing salicylic acid at the root surface 40,41 , and in other cases, ISR-inducing rhizobacteria trigger a different signalling pathway that does not require salicylic acid [42][43][44][45] .…”
Section: Systemic Resistance Induced By Non-pathogenic Rhizobacteriamentioning
confidence: 99%
“…Plants that carry a mutation in the NPR1 gene accumulate normal or even higher levels of SA after pathogen infection, but are impaired in their ability to transcriptionally activate PR genes and to mount a SAR response. Although some rhizobacterial strains can activate the SA-dependent SAR pathway (De Meyer and Hö fte, 1997), the large majority of the reported resistance-inducing fluorescent Pseudomonas spp. strains have been shown to trigger ISR in a SA-independent manner (Van Loon and Bakker, 2005).…”
mentioning
confidence: 99%
“…Increase in mRNAs encoding PAL and Chalcone synthase were recorded in the early stages of the interaction between bean roots and various rhizobacteria (Zdor & Anderson 1992). De Meyer and Hofte (1997) reported that rhizosphere colonization by P. aeruginosa TNSK2 activated PAL in bean roots and increased the salicylic acid levels in leaves. Increased activity of PAL was recorded in P. fluorescens isolate Pf1 treated tomato and hot pepper seedlings challenged with the pathogen reached maximum on the third day after challenge inoculation and was maintained at higher levels throughout the experimental period (Ramamoorthy et al 2002).…”
Section: Discussionmentioning
confidence: 99%